Efeitos de práticas de descompactação do solo em área sob sistema plantio direto - Seki, Andre Satoshi [UNESP]; Seki, Fernanda Goncalves [UNESP]; Jasper, Samir Paulo; Arbex Silva, Paulo Roberto [UNESP]; Benez, Sergio Hugo [UNESP] (Univ Federal Ceara, Dept Geol, 2015)
Soil compaction is one of the limiting factors in areas subjected to direct seeding. The method used to break up the compacted layer should disturb the soil as little as possible, as well as maintain the ground cover. The aim of this study was to evaluate the influence of subsoiling, scarification and use of shaft-type furrowing mechanisms when sowing, on preserving the ground cover, water content and soil density, as well as the effects on maize yield in a dystroferic Red Nitosol, cultivated under a system of direct seeding for ten years. The experimental design was of randomised blocks, with eight soil management treatments: subsoiling to a depth of 0.40 m before sowing the winter crop, subsoiling to 0.40 m before sowing the maize, scarification to 0.30 m before the winter crop, scarification to 0.30 m before the maize, scarification to 0.20 m before the winter crop, scarification to 0.20 m before the maize, direct seeding of the maize with a shaft-type furrowing mechanism and direct seeding of the maize using a double disc furrower. There were four replications. Subsoiling and scarification influenced the preservation of the ground cover, soil density and water content immediately after sowing, but did not interfere in plant development or grain yield in the maize crop. The use of shaft-type furrowing mechanisms in the sowing operation had no effect on any of the parameters under study.

A compactação do solo é o um dos fatores limitante em áreas submetidas ao sistema plantio direto. O manejo utilizado para romper a camada compactada deve mobilizar o mínimo possível o solo, além de manter a cobertura sobre o solo. O objetivo deste trabalho foi avaliar a influência da subsolagem, da escarificação e da utilização de mecanismos sulcadores tipo haste na operação de semeadura sobre a manutenção da cobertura do solo, o conteúdo de água e a densidade do solo, assim como os efeitos sobre a produtividade do milho em um Nitossolo Vermelho distroférrico há dez anos cultivado no sistema plantio direto. O delineamento experimental utilizado foi de blocos casualisados, contendo oito tratamentos de manejo do solo: subsolagem a 0,40 m antes da cultura de inverno, subsolagem a 0,40 m antes do milho, escarificação a 0,30 m antes da cultura de inverno, escarificação a 0,30 m antes do milho, escarificação a 0,20 m antes da cultura de inverno, escarificação a 0,20 m antes do milho, plantio direto de milho com mecanismo sulcador tipo haste e plantio direto de milho com mecanismo sulcador tipo disco duplo; e quatro repetições. A subsolagem e a escarificação influenciaram a manutenção de cobertura, a densidade e o conteúdo de água no solo logo após a semeadura, porém não interferiram no desenvolvimento das plantas e na produtividade de grãos, na cultura do milho. A utilização de mecanismos sulcadores tipo haste na operação de semeadura não apresentou efeito sobre nenhum dos parâmetros estudados.
Effects of soil decompaction techniques in an area under a system of direct seeding
Keywords: Subsoiling; Scarification; Physical attributes; Productivity; Subsolagem; Escarificação; Atributos físicos; Produtividade